ANALISIS PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN PADA GALERI INDONESIA WOW LLP KUKM DI JAKARTA - Astika, A; Gumilang, Dendi Anggi; Kurniasih, Augustina (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
Galeri Indonesia WOW seeks to maximize customer satisfaction through purchasing decisions. This study aims to analyze and determine the effect of price, product quality and service quality to customer satisfaction through purchasing decisions. The type of this research is explanatory that is aimed to find the influence of independent variable, price, product quality and service quality to influence of dependent variable that is purchasing decision and consumer satisfaction. Sampling technique of accidental sampling. Samples were taken from the population of 1102 by using Slovin formula obtained sample of 293 people. Data analysis using linear regression SPSS version 22 applications. The results showed that the variable price, product quality and service quality have a positive influence on customer satisfaction through purchasing decisions either partially or simultaneously. Based on the results of research, the influence of price variables, product quality and service quality to purchase decision of 89%, the influence of price variables, product quality, service quality and purchasing decisions to customer satisfaction of 95.7%. Intervention variable that is purchasing decision have influence to consumer satisfaction equal to 92.5%. Price is the most important factor affecting purchasing decision and consumer satisfaction. Galery Indonesia WOW should focus attention to price to increase consumer’s satisfaction through purchasing decision